Disentangling the link between stock and accounting performance in acquisitions - André Betzer; Marc Goergen (University of Wuppertal, Schumpeter School of Business and Economics, 2011)
While empirical studies that use event-study methodology find on average that the gains from mergers and acquisitions are positive, those focusing on accounting figures tend to find a significant drop in performance. We argue that each of the four possible combinations between positive or negative abnormal stock returns and accounting performance is due to a distinct acquisition motive. We find strong empirical evidence in support of this claim.
urn:nbn:de:hbz:468-20110722-124418-2
Keywords: G34; G3; G14; 330; Mergers and acquisitions; performance measurement; synergies; preemption; overvaluation; corporate governance; agency problems; Übernahme; Motivation; Synergie; Börsenkurs; Betriebliche Kennzahl; Unternehmenserfolg; USA